Modulation of Gut Microbiota by Whole Encapsulated Brown Seaweed (Himanthalia elongata) in Overweight Subjects: A Randomized Double-Blind Placebo-Controlled Trial - Lopez-Santamarina, Aroa; Cardelle-Cobas, Alejandra; Mondragon, Alicia del Carmen; Cepeda, Alberto; Rodriguez, Jose A.; Miranda, Jose Manuel (Nutrients, 2025)
Background/Objectives: Brown seaweeds, such as Himanthalia elongata, are a promising source of dietary fiber. However, in vivo evidence regarding the effects of H. elongata intake on the human gut microbiota remains limited. This study aimed to evaluate the impact of daily H. elongata consumption on the gut microbiota composition and short-chain fatty acid production in overweight adults. Methods: A randomized, double-blind, placebo-controlled trial was conducted in which 10 overweight adult participants consumed 2 g/day of whole H. elongata for 30 days. Fecal samples were collected before and after the intervention for 16S rRNA sequencing and short-chain fatty acid analysis. Dietary intake was evaluated using a 24 h recall and a 3-day dietary record. Nutritional assessment was performed to determine habitual macronutrient consumption. Results: Baseline dietary analysis revealed an imbalanced macronutrient profile characterized by high intakes of total and saturated fats and protein, along with low carbohydrate and fiber consumption. In addition, 50% of the participants were obese, and 50% were overweight based on the BMI. Notable changes in the gut microbiota composition were observed after the intervention, including increases in short-chain fatty acid-producing species, such as Parabacteroides distasonis, Bacteroides eggerthii, Bacteroides uniformis, and Bacteroides obeum. Conclusions: This study provides the first clinical evidence in humans that whole H. elongata can beneficially modulate the gut microbiota composition. These results support the potential use of this seaweed as a functional prebiotic ingredient in dietary strategies aimed at enhancing gut health.